2017
DOI: 10.12659/msm.905337
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CYP2C19 Genetic Polymorphism in a Large Ethnic Hakka Population in Southern China

Abstract: BackgroundCytochrome P450 (CYP) 2C19 is an enzyme involved in the bioactivation of various important therapeutic drugs, from pro-drugs to an active inhibitor of platelet action. Variants in the CYP2C19 gene influence the pharmacokinetics and clinical response to antiplatelet drugs such as clopidogrel; however, there is no available data about the genetic variation of CYP2C19 in the Hakka population in China.Material/MethodsA total of 6686 unrelated participants (ages 17–98 years) of self-reported Hakka ancestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 42 publications
4
18
1
1
Order By: Relevance
“…The CYP2C19*2 allele frequency in the subjects of our study was higher than that reported for Caucasians. Interestingly, the CYP2C19*2 allele frequency in our group (30.46%) was closer to those of Hakka (31.06%) and Chinese-Dai (30%) populations [18][19]. As shown in Table 2, the CYP2C19*2 allele frequency in our group was closer to that reported for other Asian populations.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The CYP2C19*2 allele frequency in the subjects of our study was higher than that reported for Caucasians. Interestingly, the CYP2C19*2 allele frequency in our group (30.46%) was closer to those of Hakka (31.06%) and Chinese-Dai (30%) populations [18][19]. As shown in Table 2, the CYP2C19*2 allele frequency in our group was closer to that reported for other Asian populations.…”
Section: Resultssupporting
confidence: 79%
“…Caucasians (0.0-0.3%) [25][26][27][28][29], Africans (0.0-2.0%) [30][31][32], Asians (1.0-11.1%) [18][19][20][21][22][23][24]. The CYP2C19*3 allele frequency was reported to be 5.65% in the Foshan population, which is consistent with those in other Chinese populations [19][20][21].…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The mechanism of CYP2C19*2 mutation is a 681 substitution of guanine to adenine (G > A) in the exon 5, which lead to a 40 base pair fragment containing a Smal restriction endonuclease site to be lost in the initial segment of exon 5 during transcription, causing an inactive enzyme. The CYP2C19*3 polymorphism is a 636 substitution of guanine to adenine (G > A) in the exon 4, causing the codon of tryptophan changing to a stop codon, which lead to a premature termination of protein synthesis and a lack of connective zone of the substrate and the hemochrome [10]. According to metabolic capacity, CYP2C19 can be divided into three phenotypes: extensive metabolizers (EMs), intermediate metabolizers (IMs), and poor metabolizers (PMs).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the cytochrome P450 (CYP) 2D6*1 frequency is significantly higher in Japanese than in Koreans and Chinese, whereas the frequency of CYP2D6*10, a loss‐of‐function allele, in Koreans and Japanese is significantly lower than that in Chinese (Lee et al, ; Sohn et al, ). Additionally, CYP2C19*3, a decreased or no function allele, is relatively less frequently found in Chinese than in Koreans and Japanese, whereas the frequency of CYP2C19*17, an increased function allele, was relatively higher in Chinese than in Koreans and Japanese (Kim, Song, Kim, & Park, ; Sohn et al, ; Zhong et al, ). These genomic differences in DMEs could have contributed to distinct PK profiles between Koreans, Japanese and Chinese even though they are geographically close.…”
Section: Introductionmentioning
confidence: 99%